2017
DOI: 10.1039/c7sm00328e
|View full text |Cite
|
Sign up to set email alerts
|

Bulk advection and interfacial flows in the binary coalescence of surfactant-laden and surfactant-free drops

Abstract: This work focuses on the study of bulk flows accompanying the coalescence of two aqueous drops, one containing surfactant and the other surfactant-free, in silicone oils of various viscosities. It is observed that the surfactant-free drop intrudes into the surfactant-laden drop in the form of a penetrating jet whose speed increases and average radius decreases with increasing outer phase viscosity. Mixing patterns within the coalescing drops are due to the force imbalance caused by capillary pressure differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…When 0.0, 0.5, 1.0, and 2.0% Tween80 was added, the size of microcapsules ( : 3 mL·h −1 , : 5 mL·h −1 ) were about 610, 470, 420, and 400 μm respectively. The addition of surfactant like Tween80 can diminish the interfacial tension of the liquid [ 34 , 35 , 36 ], which affected the synthesis of Ca-alginate from two different ways. One is that water molecules can be fixed on the surface of the rejuvenator droplets by Tween80 to prevent the aggregation and fusion of the emulsion droplets in alginate solution, thus improving the stability of the micro-emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…When 0.0, 0.5, 1.0, and 2.0% Tween80 was added, the size of microcapsules ( : 3 mL·h −1 , : 5 mL·h −1 ) were about 610, 470, 420, and 400 μm respectively. The addition of surfactant like Tween80 can diminish the interfacial tension of the liquid [ 34 , 35 , 36 ], which affected the synthesis of Ca-alginate from two different ways. One is that water molecules can be fixed on the surface of the rejuvenator droplets by Tween80 to prevent the aggregation and fusion of the emulsion droplets in alginate solution, thus improving the stability of the micro-emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that differences in droplet sizes and surfactant contents, as well as carrier fluid viscosities, can be modulated in this platform to further enhance droplet coalescence and mixing. 37,38,48 In addition to single-cell RNA-Seq and other single-cell assays, we anticipate this technology to be useful in other applications that benefit from multistep processing on a nanoliter scale, such as single-molecule assays, cell-cell interaction studies, clonal micro-colony studies, combinatorial approaches to protein crystallization, 49 titrations, chemical synthesis, synthesis of monodispersed particles [50][51][52] and heterogeneous colloidal assemblies, 53,54 kinetics studies, batch and semibatch nanoliter reactors, and diagnostic assays.…”
Section: Discussionmentioning
confidence: 99%
“…High viscosity continuous fluids have been reported to minimize the thinning and rupture of the wetting layer (which can lead to aqueous phase sticking) in SlipChip devices 27 and have been shown to speed up mixing after coalescence of dispersed-phase droplets. 37,38 We also observed that lower viscosity oils may wash away the prespotted reagents during device assembly as the extra oil is pushed out when the device plates are forced together (due to higher Reynolds number). Therefore, we chose to use 50 mPa s silicone oil with 0.01 mg mL −1 Span-80 for continuous phase.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…This droplet movement arose from surface tension differences caused by dissimilar contact angles between the wave's surface and the droplets. The differences in surface tension caused droplets with large contact angles to move to the wave surface with a low angle [29]. Upon impact, the droplets on the sensor came in contact with the wave surface and collided with the rising wave surface particles.…”
Section: Effects Of Droplets On the Sensor Surfacesmentioning
confidence: 99%